The importance of protected habitats and LiDAR data availability for assessing scenarios of land uses in forest areas. (January 2022) - Hernando, Ana; Sobrini, Iñigo; Velázquez, Javier; García-Abril, Antonio
Abstract: Natura 2000 network is becoming increasingly important for ecosystem services but not all human activities are limited as long as they ensure protection of conservation values. Private owned areas should harmonize biodiversity conservation and other compatible land uses with human activities sustainability. The purpose of this study is to present a methodology for the assessment of urban use capacity considering restrictions presented in a Natura 2000 site in Central Spain (Madrid). This assessment takes the advantages of high-resolution images and point clouds LiDAR data using Object Based Images Analysis (OBIA). Considering different ranges of (i) tree height, (ii) slopes and (iii) the existing protected habitats, six scenarios of Urban use capacity were obtained. A canopy height vegetation was derived, and the maximum height was assigned to each delineated crown polygon tree. The implementation of this methodology proposes the largest potential urban area (Scenario 6) but priority habitats and habitats of Community interest were entirely removed from it. Finally, plots (1000 m 2) with greater or lesser capacity of vegetation coverage change were located. A total of 145 plots (6% of the whole property) with urban use low capacity were located. This methodology can be extrapolated to any protected area that seeks to harmonize biodiversity conservation and human activities. Highlights: Natura 2000 network seeks to harmonize biodiversity conservation and other land uses. Scenarios of vegetation coverage change can be assessed combining range of tree heights, slopes, and protected habitats areas. LiDAR images and point cloud using object-based image analysis provides satisfactory height and locations trees. The maintenance habitats of European interest is a priority for the urban use capacity assessment.